International Politics and Archeology: Disparate Critical Teaching Topics - EAA Editorial Office (Education About Asia, 2021)
Although these two topics will probably attract different readers, they both are important components of a liberal arts education. Virtually all high schools and colleges in North America and elsewhere offer modern world history; in the US, AP Comparative Government and Politics; and in Europe, the US and elsewhere, International Baccalaureate Programs courses in the “individual and societies” curriculum focus upon international politics and issues. Increasingly, college and universities offer similar courses for beginning undergraduates. Archeology also can be an important subject to enhance understanding of Asia. Although teachers and students at every level can learn more about Asia from exploring archeology’s lessons, the most common unifying thread between US states at the middle school level is an emphasis upon ancient and early world history, hence the importance of archeology.
Keywords: Archeology; Asia General; China; China and Inner Asia; East Asia; India; International Relations; Japan; South Asia; Sri Lanka